STUDYING THE FEATURES OF KIDNEY DAMAGE IN PREECLAMPSIA - Mirzayeva G. P.; Jabbarov O. O. (Modern American Journals, 2025)
The growing interest of nephrologists in the problem of kidney injury in preeclampsia is due to its high prevalence (2–14% of all pregnancies) and unpredictable outcome. The pathogenesis of kidney injury in PE is poorly known, however, the role of imbalance of pro- and anti-angiogenic factors – VEGF and sFlt-1 – has been established as one of the most important pathogenetic mechanisms underlying the development of PE. The article presents modern data on the pathogenesis and renal manifestations of PE at different times of its development in comparison with markers of placental angiogenesis. The role of the imbalance of the sFlt-1 / VEGF system in the formation of proteinuria, arterial hypertension and renal dysfunction in PE.
Keywords: Preeclampsia, glomerular injury, vascular endothelium growth factor (VEGF), soluble fms-like tyrosine kinase-1 receptors (sFlt-1), podocyturia, proteinuria, glomerular filtration rate, blood pressure.